2018
DOI: 10.1242/jeb.185900
|View full text |Cite
|
Sign up to set email alerts
|

Extreme physiological plasticity in a hibernating basoendothermic mammal, Tenrec ecaudatus

Abstract: Physiological plasticity allows organisms to respond to diverse conditions. However, can being too plastic actually be detrimental? Malagasy common tenrecs, , have many plesiomorphic traits and may represent a basal placental mammal. We established a laboratory population of and found extreme plasticity in thermoregulation and metabolism, a novel hibernation form, variable annual timing, and remarkable growth and reproductive biology. For instance, tenrec body temperature ( ) may approximate ambient temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In contrast to those tenrec species highlighted above that use some form of heterothermic response during most of the year, other species, such as the tailless tenrec, Tenrec ecaudatus, are generally believed to only hibernate seasonally (Nicoll, 1986). Although based on more recent studies, it is highly likely that they can also use short bouts of torpor outside of the regular hibernation period (Lovegrove et al, 2014b;Treat et al, 2018).…”
Section: Seasonal Heterothermic Responsesmentioning
confidence: 99%
“…In contrast to those tenrec species highlighted above that use some form of heterothermic response during most of the year, other species, such as the tailless tenrec, Tenrec ecaudatus, are generally believed to only hibernate seasonally (Nicoll, 1986). Although based on more recent studies, it is highly likely that they can also use short bouts of torpor outside of the regular hibernation period (Lovegrove et al, 2014b;Treat et al, 2018).…”
Section: Seasonal Heterothermic Responsesmentioning
confidence: 99%
“…'brumation' [10]. However, there is large variation in physiology even between hibernating mammals, notably in tenrec [11], implying that hibernation is not one specific physiological state. As such, herein 'hibernation' will be used to describe the state of reptilian winter dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with Hubrecht, embryologists focused on insectivores because they were perceived to be primitive and could cast light on the basic mammalian condition (Hubrecht, ). Tenrecs continue to be viewed in this light (Treat et al, ). They have a low encephalisation index (Mack et al, ; Stankowich & Stensrud, ), a cloaca (Riedelsheimer, Unterburger, Kuenzle, & Welsch, ) and highly variable body temperature (Treat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bluntschli is often cited (e.g., Treat et al, ) for his observation that Tenrec can have a litter of up to 32 young and he mentions finding as many as 40 blastocysts in the uterus (Bluntschli, ). This is the upper end of the range as a later study found a mean of 9.7 implantations (Nicoll & Racey, ).…”
Section: Tenrec Reproductionmentioning
confidence: 99%